Analysis of Law Enforcement Against Over Dimension Over Load (ODOL) Violations According to the Road Traffic and Transportation Law - Riza Muttaqin; Abdul Halim; Subroto Rindang Arie Setyawan (Jurnal Restorasi : Hukum dan Politik, 2024)
Over Dimension Over Load (ODOL) is one of the most serious violations in road traffic and transportation in Indonesia, with high risks to safety and damage to infrastructure. Although Law No. 22/2009 on Road Traffic and Transport regulates ODOL violations, there is an imbalance in the categorization of punishment: *over dimension* violations are considered a crime (Article 277), while *over load* is only categorized as a misdemeanor (Article 307). This research utilizes a normative legal research method with a statutory approach, highlighting weaknesses in the enforcement and substance of the law that risk leading to unfairness and ineffectiveness of sanctions. The results show that the disparity in ODOL penalty categories does not provide an adequate deterrent effect and has the potential to reduce legal compliance. To address this inconsistency, it is recommended that Article 277 and Article 307 be revised so that they are both regulated as equivalent criminal offenses with more severe sanctions, including high fines or imprisonment. This reformulation aims to strengthen law enforcement and improve road safety.